Preparation of magnetic hierarchical porous carbon spheres with graphitic features for high methyl orange adsorption capacity - Adisak Siyasukh (2018)
© 2018 Elsevier Ltd This report describes the successful use of a template-free method in a microemulsion system for the preparation of magnetic hierarchical porous carbon (MHPC) spheres, which possess high adsorption capability for methyl orange (MO) in aqueous solution, easy separability from water by magnetic force after the MO removal, and reusability that allowed MO to be adsorbed several times. MHPC spheres are produced by water-in-oil emulsification coupled with sol-gel polymerization of resorcinol containing Fe(NO3)3and formaldehyde to make spherical carbon precursors with a macroporous framework inside, followed by carbonization with N2or CO2activation to transform them into MHPC spheres. Carbonization at temperatures higher than 800 °C resulted in not only graphitic feature formation, but also both micro- and mesopores in the macroporous framework. Moreover, CO2activation at 900 °C both remarkably enhanced the graphitic features and increased the mesopore volume to 2.16 cm3/g. The magnetic property could be developed by both carbonization and CO2activation at 900 °C. MHPC spheres obtained from CO2activation developed tremendous adsorption capacities, as high as 1522.6 mg/g under neutral conditions, which were suitable to be reused for MO removal for at least four consecutive cycles without efficiency loss.